2019
DOI: 10.3846/jbem.2019.9592
|View full text |Cite
|
Sign up to set email alerts
|

Research on Financing Ecology and Financing Efficiency of Strategic Emerging Industries in China

Abstract: After integrating external ecological and endogenous factors of the development of the industry, the paper builds a financing ecology index system, and analyses the financing ecology of strategic emerging industries in recent years. Then the paper further analyses the influence of external and internal financing ecology on financing efficiency. The results show that the financing ecology of the strategic emerging industries, external financing ecology in particular, is in the continuous improvement. The financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 23 publications
(27 reference statements)
1
21
0
Order By: Relevance
“…The results show that seven factors, such as account receivables turnover days, return on assets, quick ratio, net profit growth rate, total assets and total compensation of the top three executives, all have significant effects on the equity financing efficiency of strategic emerging industry listed companies. Xu and Geng (2020) selected the strategic emerging industry listed companies included in the Shenzhen Emerging Index as a research sample and analyzed the impact of financing constraints, financial development and the interaction between the two on the financing efficiency of strategic emerging industry listed companies. The research found that: financing constraints, financial development level and the financing efficiency are significantly positively correlated, and the combined effect of the two is conducive to improving the financing efficiency of listed companies in strategic emerging industries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show that seven factors, such as account receivables turnover days, return on assets, quick ratio, net profit growth rate, total assets and total compensation of the top three executives, all have significant effects on the equity financing efficiency of strategic emerging industry listed companies. Xu and Geng (2020) selected the strategic emerging industry listed companies included in the Shenzhen Emerging Index as a research sample and analyzed the impact of financing constraints, financial development and the interaction between the two on the financing efficiency of strategic emerging industry listed companies. The research found that: financing constraints, financial development level and the financing efficiency are significantly positively correlated, and the combined effect of the two is conducive to improving the financing efficiency of listed companies in strategic emerging industries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of empirical research on financing efficiency evaluation, the methods adopted by scholars mainly include fuzzy comprehensive evaluation method, multiple regression analysis method, entropy method, data envelopment analysis method (DEA), among which the DEA method builds an input-output indicator system, which closely integrates the integration and use of corporate funds and overcomes the subjectivity of indicator weight design, can effectively evaluate the efficiency of the entire financing process and has become the leading method for evaluating financing efficiency. Based on the super-SBM DEA model of Tone (2002), in this paper, the data envelopment analysis method (DEA) is adopted to solve this problem (Xu, 2018;Zhang, 2018;Wang, 2020). Applying the DEA method to the evaluation of corporate financing efficiency has the following advantages:…”
Section: Super-efficiency Deamentioning
confidence: 99%
See 1 more Smart Citation
“…CFO belongs to internal finance and is the normal source of cash for firms. According to Xu et al [23], CFO represents capital turnover and improves the ability of the firm to handle risks, which can ensure the smoothing of R&D investment. CFI mainly includes cash inflows and outflows from buying machinery and equipment, plants, advanced technology, intangible assets, etc.…”
Section: Introductionmentioning
confidence: 99%
“…CFF comprises external funds. External creditors and investors are only willing to invest in investments that are considered to be financially sound and, hence, are reluctant to invest in R&D activities, which have the characteristics of high uncertainty [23]. Based on the statements, CFO can be the most accessible source of finance for firm R&D investment, and CFF can be the least accessible source of finance for firm R&D investment.…”
Section: Introductionmentioning
confidence: 99%